Study of treatment outcomes in tuberculosis patients on DOTS therapy at five centres in Goa - Motghare, Dilip D.; Sardessai, Geetanjali M.; Vaz, Frederick S.; Kulkarni, Manoj S. (International Journal Of Community Medicine And Public Health, 2017)
Background:The objective was to study the treatment outcomes in tuberculosis patients on DOTS therapy in five centres in Goa in terms of cure rates, treatment completion rates, unfavourable outcomes and factors responsible for unfavorable outcomes. Methods: Study setting: It was a facility based study at five DOTS centres from the Panaji Tuberculosis Unit (TU). Study design: prospective follow up design was used for the study. Study subjects: All patients registered at the selected five DOTS centres for DOTS therapy under RNTCP in the period from 1st April 2011 to 31st December 2011 were selected as study subjects and followed prospectively for a period of nine months till 30th September 2012. Study instruments: data was collected from patients by personal interview and a pretested structured questionnaire. Data was also obtained from patient treatment cards and by interviewing the DOTS provider. Statistical analysis: Data was analysed using SPSS software. The statistical tests used were frequencies, descriptive, Chi square test, odds ratio and logistic regression analysis. Results:Overall 42.9% of the patients were declared cured, 42.3% had treatment completed as the outcome, 4.9% were defaulters, 2.7% patients died, 1.6% were classified as treatment failure, 2.2% were transferred out and 0.5% of the patients were shifted to Non-DOTS treatment regimen while in 2.7% of the patients treatment outcome was not available. Presence of diabetes mellitus, hypertension and alcohol use were found to be significantly associated with unfavourable outcomes in Tuberculosis patients on DOTS. Conclusions:Patients with alcohol addiction and concomitant hypertension were found to have higher levels of un-favourable outcomes; therefore such patients require continuous monitoring and support to ensure treatment success.